2010
DOI: 10.3858/emm.2010.42.3.024
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of ROS generation by 4,4'-diaminodiphenylsulfone in non-phagocytic human diploid fibroblasts

Abstract: The action mode of 4,4'-diaminodiphenylsulfone (DDS) is still under debate, although it has long been used in treatment of several dermatologic diseases including Hansen's disease. In this study, we tested the effect of DDS as an antioxidant on paraquat-induced oxidative stress in non-phagocytic human diploid fibroblasts (HDFs). Overall, preincubation of HDFs with DDS prevented the oxidative stress and the resulting cytotoxic damages caused by paraquat in these cells. The specific effects of DDS in paraquat-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
3
11
0
1
Order By: Relevance
“…The DDS-treated worms exhibited a decreased ROS-induction response to PQ treatment and were less sensitive to PQ (Cho et al, 2010b). In the same study, we confirmed that DDS has an antioxidant effect in PQ-treated human dermal fibroblasts, in which it effectively suppresses ROS generation by inhibiting the NOX system (Cho et al, 2010a).…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…The DDS-treated worms exhibited a decreased ROS-induction response to PQ treatment and were less sensitive to PQ (Cho et al, 2010b). In the same study, we confirmed that DDS has an antioxidant effect in PQ-treated human dermal fibroblasts, in which it effectively suppresses ROS generation by inhibiting the NOX system (Cho et al, 2010a).…”
Section: Discussionsupporting
confidence: 75%
“…Previously, we reported that DDS could control PKCβ activity in human diploid fibroblasts (Cho et al, 2010a). In addition, our present study showed that DDS could effectively inhibit PQ-induced PKCμ activation in lung tissues and lung fibroblasts (Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations